1994
DOI: 10.3168/jds.s0022-0302(94)77309-4
|View full text |Cite
|
Sign up to set email alerts
|

Juice-Extracted Grass Pellets and Sodium Bicarbonate for Cows in Midlactation Fed Timothy Grass Silage

Abstract: Eighteen midlactation Holstein cows, averaging 80 to 125 d of lactation, were used in a trial of switchback design to evaluate two timothy silages, wilted or direct-cut and treated with formic acid, and three treatments, control, NaHCO3 added at 2% of DM, or juice-extracted grass pellets replacing 30% silage DM. Cows fed direct-cut silage that had been treated with formic acid consumed more DM (19.8 vs. 18.6 kg/d) than those fed wilted silage. The DMI was also increased with NaHCO3 and grass pellet treatments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In the current study, the ruminal degradation of NDF was 71.5 and 80.0%. This is in line with Orozco-Hernandez et al (1994) who reported ruminal NDF degradation rates up to 80%.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the ruminal degradation of NDF was 71.5 and 80.0%. This is in line with Orozco-Hernandez et al (1994) who reported ruminal NDF degradation rates up to 80%.…”
Section: Discussionsupporting
confidence: 92%